2016
DOI: 10.1002/bmc.3850
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a high performance liquid chromatography quantification method of levo‐tetrahydropalmatine and its metabolites in plasma and brain tissues: application to a pharmacokinetic study

Abstract: Levo-tetrahydropalmatine (l-THP) is an alkaloid isolated from Chinese medicinal herbs of the Corydalis and Stephania genera. It has been used in China for more than 40 years mainly as an analgesic with sedative/hypnotic effects. Despite its extensive use, its metabolism has not been quantitatively studied, nor there a sensitive reliable bioanalytical method for its quantification simultaneously with its metabolites. As such, the objective of this study was to develop and validate a sensitive and selective HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Multiple demethylations, glucuronic acid and sulfate coupling, and renal excretion of THP in humans are the main drug clearance pathways of THP. THP has four monodesmethyl metabolites: L-isocorypalmine, L-corypalmine, L-tetrahydropalmatrubine, and L-corydalmine ( Abdallah et al, 2017 ). The mean time to peak concentration (T max ) and half-life (T 1/2 ) of THP in rats were 0.44 and 4.49 h, respectively ( Wang W. et al, 2017 ), whereas those of healthy cocaine-using adults were 1.5 and 13.3 h, respectively ( Hassan et al, 2017 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…Multiple demethylations, glucuronic acid and sulfate coupling, and renal excretion of THP in humans are the main drug clearance pathways of THP. THP has four monodesmethyl metabolites: L-isocorypalmine, L-corypalmine, L-tetrahydropalmatrubine, and L-corydalmine ( Abdallah et al, 2017 ). The mean time to peak concentration (T max ) and half-life (T 1/2 ) of THP in rats were 0.44 and 4.49 h, respectively ( Wang W. et al, 2017 ), whereas those of healthy cocaine-using adults were 1.5 and 13.3 h, respectively ( Hassan et al, 2017 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…It is well known that the main active ingredients of the extract of C. yanhusuo are the alkaloids, which possess potent pharmacological effects, such as antinociceptive, antitumor, antibacterial, anti-inflammatory, and anti-depressive activities. For example, tetrahydropalmatine, corydaline, and protopine could enter the central nervous system through the blood-brain barrier, and play the role of analgesic, sedative hypnotic, and anxiolytic effects [ 1 , 2 , 3 , 4 ]. Oxoglaucine, berberrabine, berberine, coptisine, palmatine, columbamine, and jatrorrhizine were reported to have antitumor activity [ 5 , 6 , 7 ], while berberine, palmatine and epiberberine were found to have antibacterial activity [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern medical research has revealed that the C. yanhusuo extract has significant inhibitory effects upon acetylcholinesterase (AChE) and cancer cell proliferation, as well as beneficial effects for the cardiovascular system (Ling et al, 2006;Xiao et al, 2011;Chen et al, 2016). To date, more than 100 compounds have been isolated and identified from RC, including fatty acids, organic acids, amino acids, sugars, steroids, anthraquinones, volatile compounds, and alkaloids (Hung and Wu, 2016;Abdallah et al, 2017;Hassan et al, 2017). In particular, over 80 types of alkaloids have been isolated and identified (Tian et al, 2020), these being major pharmacologically active compounds for the treatment of blood vessel diseases, tumors, and various pains (Li et al, 2014;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%